Governance as the Enabling Condition: An Integrated Model of Digital Transformation Management in Islamic Higher Education - Sundari Sundari; Maskuri Maskuri (JUMPA : Jurnal Manajemen Pendidikan, 2025)
Digital transformation has become a strategic priority for higher education, yet few empirical studies examine how Islamic higher education institutions manage this change as a whole rather than as isolated technology adoption. This study analyzes the management of digital transformation at STIKK An-Nur 2 Bululawang, an Islamic higher education institution in Indonesia. The research applied a qualitative single-case design. Data collection combined semi-structured interviews, non-participant observation, and document analysis, involving institutional leaders, IT staff, lecturers, administrative staff, and students. Thematic analysis guided the interpretation, and credibility was maintained through source triangulation, method triangulation, member checking, and an audit trail. The findings identify four interrelated domains that drive digital transformation at the institution, namely digital administration, academic information systems, e-learning, and digital governance. Digital administration improved service efficiency and transparency, academic information systems supported data-driven decision making, e-learning fostered flexible and student-centered learning, and digital governance reinforced leadership, coordination, and institutional accountability. The study proposes an integrated Digital Transformation Management Model in which digital governance functions as the enabling condition that binds the other three domains into a coherent institutional strategy. The results extend current knowledge by treating digital transformation as an integrated managerial competence rather than a portfolio of separate projects. Practically, the model guides Islamic higher education leaders to align technological infrastructure, organizational culture, strategic leadership, and governance when pursuing sustainable transformation under comparable resource conditions.